ANALISIS DAN PERANCANGAN SISTEM APLIKASI KAMUS ISTILAH BIOLOGI BERBASIS ANDROID UNTUK SISWA SMA - Sri Huning Anwariningsih; Firdhaus Hari Saputro Al Haris; Nurul Hastuti (JURNAL GAUNG INFORMATIKA, 2015)
Biology subjects aimed at studying the identity and characteristics of living things ie humans, animals, and plants. The identities of living thing often use foreign namesthat are very hard to memorize. The use of methods taught so far explain the lesson with the book companion SW (Student Worksheet) or the package book as a supporter. The number of biology terms that exist to make some students have difficulty in understading the existing subject matter and momorize the term. The purpose of this research is to design and analysis the dictionary applications of biology terms based android in Senior High School Muhammadiyah 4 Kartasura.The designing of this application using UML (Unified Modeling Language) and implemented using JQuery language which includes components from javascript,Cascanding Style Sheet (CSS), and HTML (Hypertext Markup Language). The research method used by waterfall research method and system test using five view method with the same specification with different type and OS version. On theAdvan i7A device of 8 features provides an average rating of 3.3 seconds, the Oppo Mirror 5 device of 8 features provides an average rating of 3.4 seconds, the SamsungGalaxy V Plus device of 8 features provides an average rating 3.5 seconds and all runs smoothly resulting of an educative and interactive android based biology dictionaryapplication which consists of the main display page/ splash screen, main menu page, biology term page list, term translation page, application page, application informationpage, company profile page that is user friendly and assist in the learning process. The results of the display resolution/ width of the smartphone, a nice smartphone screenwith 5 inch screen compared with other resolutions such as 7 inch screen or 4 inch screen.